2020
DOI: 10.1002/ijc.33144
|View full text |Cite
|
Sign up to set email alerts
|

Cluster of differentiation 44 promotes osteosarcoma progression in mice lacking the tumor suppressor Merlin

Abstract: Merlin is a versatile tumor suppressor protein encoded by the NF2 gene. Several lines of evidence suggest that Merlin exerts its tumor suppressor activity, at least in part, by forming an inhibitory complex with cluster of differentiation 44 (CD44). Consistently, numerous NF2 mutations in cancer patients are predicted to perturb the interaction of Merlin with CD44. We hypothesized that disruption of the Merlin‐CD44 complex through loss of Merlin, unleashes putative tumor‐ or metastasis‐promoting functions of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…We also showed that the shortest isoforms of CD44, so called CD44s, which does not contain any sequences encoded by alternatively spliced variant exons, was sufficient to confer resistance to doxorubicin in osteosarcoma cells ( Figure 2 ). Nevertheless, as we have shown previously, the Nf2 -deficient osteosarcomas express additional CD44 splice variants [ 38 ]. Thus, we cannot exclude that splice variants of CD44 might regulate additional processes involved in osteosarcoma chemoresistance.…”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…We also showed that the shortest isoforms of CD44, so called CD44s, which does not contain any sequences encoded by alternatively spliced variant exons, was sufficient to confer resistance to doxorubicin in osteosarcoma cells ( Figure 2 ). Nevertheless, as we have shown previously, the Nf2 -deficient osteosarcomas express additional CD44 splice variants [ 38 ]. Thus, we cannot exclude that splice variants of CD44 might regulate additional processes involved in osteosarcoma chemoresistance.…”
Section: Discussionmentioning
confidence: 66%
“…In order to study the relevance of CD44 in mediating chemoresistance, we previously isolated osteosarcoma cells from mice that developed endogenous osteosarcoma, due to a mutation of the tumor suppressor gene Nf2 [ 38 ]. To enable the analysis of CD44-dependent processes in genetically comparable tumor backgrounds, Cd44 was deleted in Nf2 -deficient osteosarcoma cells, using the CRISPR/Cas9 approach [ 38 ]. Our results show that Cd44 -positive cells were more resistant to doxorubicin treatment than the Cd44 -negative cells (IC50 of 1.224 versus 0.7523 µM, respectively, p = 0.000793) ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations